2013
DOI: 10.1007/s00259-013-2346-6
|View full text |Cite
|
Sign up to set email alerts
|

High incidence of extraadrenal paraganglioma in families with SDHx syndromes detected by functional imaging with [18F]fluorodihydroxyphenylalanine PET

Abstract: FDOPA PET is a sensitive imaging modality which should be offered to patients with a detected SDHx (SDHD) mutation, preferably using a hybrid technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…18 F-FDOPA PET has been shown to have a sensitivity similar to 18 F-FDG PET, except in the head and neck, where it is superior. 21,25 A high sensitivity for 18 F-FDOPA PET was also described in SDHx mutation carriers, 26 which suggests a possible larger role in the imaging of cardiac PGLs. Overall, based on this study, 18 F-FDG PET may be the most valuable functional imaging modality for evaluation of patients with cardiac PGL, especially due to its wide availability.…”
Section: Discussionmentioning
confidence: 99%
“…18 F-FDOPA PET has been shown to have a sensitivity similar to 18 F-FDG PET, except in the head and neck, where it is superior. 21,25 A high sensitivity for 18 F-FDOPA PET was also described in SDHx mutation carriers, 26 which suggests a possible larger role in the imaging of cardiac PGLs. Overall, based on this study, 18 F-FDG PET may be the most valuable functional imaging modality for evaluation of patients with cardiac PGL, especially due to its wide availability.…”
Section: Discussionmentioning
confidence: 99%
“…132,133 This technique also appears to be particularly effective for patients with SDH mutations and/or biochemically silent PHEO/PGL and may be valuable as a screening technique, particularly for patients with SDHD mutations. 133,134 In a recent large study focusing on tumors missed by FDOPA PET, a high rate of SDH mutations were found, suggesting that patients with false-negative FDOPA PET scans should be tested for these mutations. 135 …”
Section: Diagnosis Of Pheo/pglmentioning
confidence: 99%
“…Subsequent studies compared 18 F-FDOPA to other imaging modalites and radiopharmaceuticals across different PGL locations and genotypes (46). 18 F-FDOPA PET/CT was found to be a sensitive (80-90% for abdominal PGLs and >95% for HNPGLs) and specific (95-100%) imaging modality for the detection and staging of non-metastatic PGLs (24, 46-49) (Figures 1-7). 18 F-FDOPA PET was also found to be superior to Octreoscan (24, 47) in the detection of HNPGLs and to be excellent for both SDHx (24) and non-SDHx (48) PGLs.…”
Section: Current Functional Imaging In the Localization Of Hnpglsmentioning
confidence: 99%